The common characteristics of cotton fishing net twines—A preliminary account - Kuriyan, J K; Cecily, P J (Indian Journal of Fisheries, 2016)
The common fibres used in India as fishing net twines are Cotton (Gossipium spp.) and Sun-Hemp Crotalaria junced) both of which are produced in the country. Cotton is by far the most important fishing gear material all over the world. India ranks as a premier cotton growing country being only second to U.S.A. in the total area cultivated. In this communication an account of the characteristics of cotton twines, subjected to the preliminary tests, are presented.